A Novel Circular RNA Mediates Pyroptosis of Diabetic Cardiomyopathy by Functioning as a Competing Endogenous RNA - Fan Yang; Anqi Li; Ying Qin; Hui Che; Yueqiu Wang; Jie Lv; Yang Li; Hui Li; Er Yue; Xueying Ding; Yahan Yu; Yunlong Bai; et al. (Elsevier, 2019)
Diabetic cardiomyopathy (DCM) is a vital cause of fatalities in diabetic patients. The programmed death of cardiomyocytes and inflammation critically contribute to cardiac hypertrophy and fibrosis in DCM. Furthermore, circular RNA (circRNA) is a key regulator of various diseases. However, the role of circRNAs in DCM remains to be elucidated. Our previous study found that pyroptosis was markedly activated in the cardiomyocytes subjected to high-glucose conditions, and miR-214-3p regulated the expression of caspase-1. The aim of this study was to elucidate whether circRNA is involved in DCM pyroptosis via the miR-214-3p/caspase-1 pathway. Herein, we identified that hsa_circ_0076631, named caspase-1-associated circRNA (CACR), was increased both in high-glucose-treated cardiomyocytes and in the serum of diabetic patients. CACR also sponged an endogenous miR-214-3p to sequester and inhibit its expression. CACR knockdown in cardiomyocytes counteracted high-glucose-induced caspase-1 activation. Conversely, miR-214-3p knockdown partially abolished the beneficial effects of CACR silencing on pyroptosis in cardiomyocytes. Therefore, this study elucidated that CACR might be a novel therapeutic target via the CACR/miR-214-3p/caspase-1 pathway in DCM. Keywords: circular RNA, miR-214-3p, caspase-1, diabetic cardiomyopathy, pyroptosis